PPM BOLSTERING HUMAN CAPITAL MANAGEMENT PADA SENTRA KULINER GUNUNG ANYAR KOTA SURABAYA - Rudiatno Rudiatno; Aldea Mita Cheryta (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Abstract Bolstering Human Capital Management is one of the themes that can be used to improve the quality of management of individuals and organizations. This theme is used to develop business partner management located in the Gunung Anyar Culinary Center, Surabaya City. The locus of community service is not generally covered by the entire Gunung Anyar Culinary Center, but two stands in the area. The problems faced by partners are 1) The income statement still uses manual; 2) Financial management strategies are still not right; 3) The price suitability is still not good; 4) Online sales are not running optimally; 5) Marketing is still around the Gunung Anyar Culinary Center; 6) The cleanliness of business partners still needs to be improved; 7) The trust of business partners at night tends to be dark; 8) Have not implemented a green economy. The implementation of this community service is carried out through several stages, namely initial observation, training and assistance in the development of the products produced. At least the outputs produced through community service carried out are 1) the partner's understanding of the automation of financial statements; 2) business development strategies; 3) calculation of the percentage of profit and total cost; 4) online sales promotion; 5) expansion of market segmentation; 6) good governance of entitlement; 7) proper light arrangement; 8) the application of the green economy. Keywords: Bolstering; Human Capital; Management